2017
DOI: 10.1097/qai.0000000000001216
|View full text |Cite
|
Sign up to set email alerts
|

Association of HIV and Opportunistic Infections With Incident Stroke: A Nationwide Population-Based Cohort Study in Taiwan

Abstract: Background HIV-associated vasculopathy and opportunistic infections (OIs) might cause vascular atherosclerosis and aneurysmal arteriopathy, which could increase the risk of incident stroke. However, few longitudinal studies have investigated the link between HIV and incident stroke. This cohort study evaluated the association of HIV and OIs with incident stroke. Methods We identified adults with HIV infection in 2000–2012, using the Taiwan National Health Insurance Research Database. A control cohort without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 28 publications
2
36
1
Order By: Relevance
“…It is estimated that 1–5% of PLWH experience clinical stroke, although ischemic lesions are seen in 4–34% of brain autopsies in this population [52]. Studies have reported increased risks of all-cause stroke (adjusted HR of 1.6–1.8) [53, 54], ischemic stroke (adjusted HR of 1.2–1.4) [53, 55, 56], and hemorrhagic stroke (adjusted HR of 2–3.3) in PLWH compared to uninfected individuals [53, 57]. Risk factors associated with these increased risks vary in different studies, but a lower CD4 count before initiation of ART [54], exposure to abacavir [54], higher HIV RNA levels [55], having AIDS-defining conditions [57], African American ethnicity [58], hepatitis C infection [57], illicit drug or alcohol abuse [57], heavy alcohol consumption [59], intracranial lesions [57], and coagulopathy [57] were all strongly associated with a higher risk of stroke.…”
Section: Cerebrovascular Disease and Strokementioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that 1–5% of PLWH experience clinical stroke, although ischemic lesions are seen in 4–34% of brain autopsies in this population [52]. Studies have reported increased risks of all-cause stroke (adjusted HR of 1.6–1.8) [53, 54], ischemic stroke (adjusted HR of 1.2–1.4) [53, 55, 56], and hemorrhagic stroke (adjusted HR of 2–3.3) in PLWH compared to uninfected individuals [53, 57]. Risk factors associated with these increased risks vary in different studies, but a lower CD4 count before initiation of ART [54], exposure to abacavir [54], higher HIV RNA levels [55], having AIDS-defining conditions [57], African American ethnicity [58], hepatitis C infection [57], illicit drug or alcohol abuse [57], heavy alcohol consumption [59], intracranial lesions [57], and coagulopathy [57] were all strongly associated with a higher risk of stroke.…”
Section: Cerebrovascular Disease and Strokementioning
confidence: 99%
“…With the introduction of ART, ischemic stroke has become the more common subtype of stroke identified in PLWH [52, 53, 64]. Some mechanisms that are thought to contribute to the higher prevalence of ischemic stroke in PLWH include: HIV-associated vasculopathy (20–32% prevalence) [60, 61], coagulopathy (19–49%) [60, 61, 65], opportunistic infection (13–28%) [61, 65], and cardioembolism (5–15%) [61, 65].…”
Section: Cerebrovascular Disease and Strokementioning
confidence: 99%
“… 9–12 The effects of other members of the herpesvirus family on vascular events are less clear, although cytomegalovirus (CMV) is hypothesised to modulate stroke risk, especially among immunocompromised populations. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Montoya et al (2017) 19 , showed increased expression of vascular endothelial cell growth factor, angiopoietin-2 and Tie-2 associated with arterial fibrosis, arterial stiffening and altered pulse pressure in patients with neurocognitive disturbance and HIV. Similarly, Yen et al (2017) 20 showed a strong correlation between glomerular filtration rate and neurocognitive decline in HIV positive individuals leading to a body of thinking around a direct relationship between vascular cognitive impairment associated to HIV disorder 21 . We previously showed that p17 from HIV caused dementia-like symptoms in a murine model following hippocampal injection 5 .…”
Section: Introductionmentioning
confidence: 98%